Population biology of Fusarium circinatum Nirenberg et O’Donnell associated with South African Pinus radiate D.Don plantation trees - Steenkamp, Emma Theodora (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.